Clinical use of neuro-imaging in psychiatric patients at the Charlotte Maxeke Johannesburg academic hospital - Letlotlo, Bokang Lipuo (My University, 2019)
Background: The use of neuro-imaging tests such as Computerised Tomography and Magnetic Resonance Imaging in psychiatry have been largely evaluated as useful but not essential. Neuro-imaging has been said to play no major role in psychiatric diagnoses beyond ruling out medical conditions such as traumatic brain injuries, tumours, infections, infarctions and bleeds. Furthermore, the majority of studies in this field suggest that neuro-imaging may be over used in psychiatry. Thus there is a need for further research in the diagnostic yield of neuro-imaging in psychiatry in order to ensure that appropriate, cost-effective methods of diagnosis are adopted, especially in South Africa’s under-resourced institutions. Aim: This study aims to determine the clinical diagnostic value of neuro-imaging in psychiatric in-patients at the Charlotte Maxeke Johannesburg Academic Hospital during a two year period dating 1 January 2014 to 31 December 2015. Methodology: A quantitative, retrospective record review of adult psychiatric inpatients was conducted at the aforementioned institution during a two-year study period. The inclusion criteria was all adult psychiatric in-patients that had brain Computerized Tomography and/or Magnetic Resonance scans performed and reported during the study period. The participants were investigated in terms of demographic characteristics, scan characteristics, DSM-IV-TR/5 diagnosis and medical diagnosis that may be associated with a positive scan result. Data analysis included descriptive statistics and a chi square analysis. Ethical clearance was obtained from the Human Research Ethics Committee at the University of the Witwatersrand. Charlotte Maxeke Johannesburg Academic Hospital Chief Executive Officer permission to conduct the study was also obtained. Results: Of the one thousand and fourty (n=1040) adult psychiatric patients’ medical records reviewed for the time period between 1 January 2014 to 31 December 2015, two hundred and thirteen (n=213) adult psychiatric patients fit the inclusion criteria of documented CT brain scan or MRI results. In total, n=74, 34.7% of the neuro-images had abnormal reports recorded. There was no statistically significant difference between the normal and abnormal CT and/or MRI scan groups with regard to demographic characteristics (age and gender), scan characteristics (type, frequency and urgency of scan) and DSM-IV-TR/5 diagnosis. HIV has a statistically significant pvalue of 0.04 to denote that abnormal neuro-imaging has clinical value in its diagnosis. Conclusion: Diagnoses in psychiatry are based entirely on behavioural, not biological, criteria. As demonstrated in other studies, this study also came to the conclusion that structural neuro-imaging is not be the key diagnostic tool in psychiatry. However, neuro-imaging is essential in excluding medical conditions.
Submitted in (partial) fulfillment of the requirements for the degree Master of Medicine in Psychiatry, Faculty of Health Sciences University of the Witwatersrand Johannesburg June 2019